2019
DOI: 10.3389/fspas.2019.00014
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Aurora Experiments and Application to Natural Aurora

Abstract: A review is given of the effects observed during injections of powerful electron beams from sounding rockets into the upper atmosphere. Data come from in situ particle and wave measurements near a beam-emitting rocket and ground-based optical, wideband radiowave, and radar observations. The overall data cannot be explained solely by collisional degradation of energetic electrons but require collisionless beam-plasma interactions (BPI) be taken into account. The beam-plasma discharge theory describes the featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 98 publications
0
14
0
Order By: Relevance
“…The same flux ratio configuration between the upward and downward fluxes, like it is displayed in Figure 6c, forms in the Southern Hemisphere (not shown here) and creates an additional electron instability situation of two electron beams moving toward each other. All these processes, however, are out of the scope of this manuscript and require additional analysis (Mishin, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The same flux ratio configuration between the upward and downward fluxes, like it is displayed in Figure 6c, forms in the Southern Hemisphere (not shown here) and creates an additional electron instability situation of two electron beams moving toward each other. All these processes, however, are out of the scope of this manuscript and require additional analysis (Mishin, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A detailed review of research concerning BPD in application to natural and artificial auroras can be found in [53]; therefore, we do not continue this topic here.…”
Section: Bpd In Spacementioning
confidence: 99%
“…An example of near-missile glow and artificial radiance rays in "Zarnitsa 2." On the right is the vertical profile of the left: ray of AA with the superimposed Monte Carlo profile (from[53]).…”
mentioning
confidence: 99%
“…Many details and discussions from the literature are not repeated here-for which, readers are routinely guided to the referenced original papers. Furthermore, this review only includes studies related to Langmuir waves produced naturally by electron beams in space plasmas and does not cover laboratory studies, results observed during injection of artificial electron beams in the ionosphere (a review provided by Mishin (2019)), or Langmuir turbulence induced in ionospheric modification experiments.…”
Section: Introductionmentioning
confidence: 99%